Right-handed interactions in puzzling B-decays - Damir Bečirević; Svjetlana Fajfer; Nejc Košnik; Lovre Pavičić (Physics Letters B)
We explain the difference between the measured decay widths of b→cτν processes and of B→Kνν¯ and their values predicted in the Standard Model by introducing the right-handed interactions both to quarks and to leptons. At low energy scales, in addition to the Standard Model particles, we assume the presence of an additional neutral lepton (right-handed neutrino). We then show a specific realization of such a scenario in a model with a single scalar leptoquark (S1), and discuss the corresponding phenomenology.